Maahanmuuttajaoppilaat erityiskouluissa - Laaksonen, Annele (Annales Universitatis Turkuensis C 262, 2008)
Immigrant Pupils in Special Education Schools The study focused on the opinions of immigrant pupils in the 1st–9th grades of basic education in four special education schools of the City of Turku and in need of special support about the following: 1. Their difficulties in going to school in general education before the transfer to a special education school. 2. Their opinions about the transfer process to special education and the changes in their school practice after being transferred to a special education school. 3. Their experiences about their school and coping in special education school. The study strengthened the idea that immigrant pupils need positive special treatment, linguistic support, individual guidance, small teaching groups and operating models that promote well-being on their integration and education path. The central educational idea of inclusive education is based on deconstructing the power structures concerning gender, ethnicity and “race” and approval of differences in the pupils. Shifting the emphasis from the pupil to working on the learning environment has resulted in special education no longer being primarily separate special education tied to a certain place, but directing the teaching more towards individuality. The central dimension of intercultural competence of a teacher working in a multicultural class seems to be the attitudes and approaches to a different pupil; the teacher must be interculturally sensitive when facing children and young people from a foreign culture. Education and teaching affect every sector of the pupil’s well-being. Learning and learning results have a connection with teaching, education and well-being. Every sector is important for the going to school and integration of an immigrant pupil in need of special support. The basis of the study is the equality of opportunities and the humanistic idea of the human being in the Finnish education policy. The immigrant pupils selected for the study represented the following language groups: Arabian, Albanian, Somali, Russian and Vietnamese. In the four special education schools, the number of immigrant pupils belonging to these language groups (2004) totalled 104. A total of 89 pupils i.e. 86% answered the questionnaire, which is sufficient considering the generalisation of the study. Although this is basically a quantitative study, the interviewing method was used in part of the study, because the questionnaires were in Finnish and consequently, it was difficult for some immigrant pupils to understand them. Understanding the questions was also affected by the fact that the age distribution in the study was very wide (7–18). According to the results of the study, the immigrants felt that the biggest drawbacks in general education were their inability to speak Finnish and lack of concentration. The actual process of being transferred to a special education class remained unclear for immigrant pupils, and they could do very little about the transfer themselves. The results show that immigrant pupils coped well in special education school; they felt that their learning ability and concentration improved in the small groups of the special education school. They considered the individual support given in the special education schools to be useful. The lower-grade immigrant pupils had a more positive attitude towards special education school than the upper-grade immigrant pupils. In all the special education schools the immigrant pupils experienced that they were in a good position in the class; girls felt this even a little more strongly than boys. The teacher-pupil-relationship was felt to be good. School bullying being so common was a negative feature experienced by immigrant pupils, who were often targets or bullies themselves. Immigrant pupils believed in their success at school and in the opportunities offered by special education schools. Generally they were of the opinion that pupils are not labelled by special school; however, upper-grade immigrant pupils were more hesitant than lower-grade immigrant pupils. This study aimed at bringing out the immigrant pupils’ own opinions. Teaching immigrant pupils in special education schools has not been very much studied in Finland, which made the topic new and even more challenging.

Tutkimuksessa selvitettiin Turun kaupungin neljän erityiskoulun perusopetuksen 1.–9.-luokkalaisten erityistä tukea tarvitsevien maahanmuuttajaoppilaiden käsityksiä 1. koulunkäyntiin liittyvistä vaikeuksistaan yleisopetuksessa ennen erityiskouluun siirtoa, 2. maahanmuuttajaoppilaiden käsityksiä erityisopetussiirtoprosessista ja niistä muutoksista, joita koulunkäynnissä ilmeni erityisopetussiirron jälkeen, 3. maahanmuuttajaoppilaiden kokemuksia koulunkäynnistään ja kouluviihtyvyydestään erityiskoulussa. Tutkimus vahvisti käsitystä, että maahanmuuttajaoppilaat tarvitsevat positiivista erityiskohtelua, kielellistä tukea, yksilöllistä ohjausta, pieniä opetusryhmiä ja hyvinvointia edistäviä toimintamalleja kotoutumis- ja koulutuspolulleen. Osallistavan kasvatuksen keskeinen kasvatusajattelu lähtee sukupuolta, etnisyyttä ja ”rotua” koskevien valtarakenteiden purkamisesta ja oppilaiden erilaisuuden hyväksymisestä. Painopisteen muuttuminen oppilaasta oppimisympäristön muokkaamiseen on saanut aikaan sen, että erityisopetus ei ole enää ensisijaisesti erillistä, paikkaan sidottua erityisopetusta, vaan opetuksen yksilöllistämistä. Monikulttuurisessa luokassa työskentelevän opettajan keskeiseksi interkulttuurisen kompetenssin ulottuvuudeksi näyttäisivät muodostuvan asenteet ja suhtautumistavat erilaista oppilasta kohtaan; opettajilta vaaditaan interkulttuurista sensitiivisyyttä kohdatessaan vierasta kulttuurista tulevia lapsia ja nuoria. Kasvatus ja opetus vaikuttavat oppilaan hyvinvoinnin jokaisella alueella. Oppiminen ja oppimistulokset ovat yhteydessä sekä opetukseen, kasvatukseen että hyvinvointiin. Jokaisella osa-alueella on tärkeä merkityksensä erityistä tukea tarvitsevan maahanmuuttajaoppilaan koulunkäynnin ja kotoutumisen kannalta. Tutkimuksen lähtökohtana on humanistinen orientaatio kasvatuskysymyksiin ja mahdollisuuksien tasa-arvo Suomen koulutuspolitiikassa. Tutkimukseen valittujen maahanmuuttajaoppilaiden kieliryhmät olivat arabia, albania, somali, venäjä ja vietnam. Kyseisiin kieliryhmiin kuuluvia maahanmuuttajaoppilaita oli neljässä erityiskoulussa (2004) yhteensä 104 ja kyselylomakkeeseen vastasi 89 oppilasta eli 86 %, mikä on tutkimuksen yleistettävyyden kannalta riittävä. Vaikka tutkimus on lähtökohdiltaan kvantitatiivinen, niin tutkimuksessa käytettiin osittain haastattelumetodia, koska kyselylomakkeet olivat suomenkielisiä ja niiden ymmärtäminen tuotti vaikeuksia joillekin maahanmuuttajaoppilaille. Kysymysten ymmärtämiseen vaikutti sekin, että tutkimuksen ikäjakauma oli suuri (7–18). Tutkimustulosten mukaan maahanmuuttajat kokivat, että heidän suurimmat vaikeutensa yleisopetuksessa olivat suomen kielen osaamattomuus ja keskittymisvaikeudet. Maahanmuuttajaoppilaille jäi epäselväksi itse erityisopetussiirtoprosessi ja heidän omat vaikutusmahdollisuutensa erityisopetussiirtoon jäivät pieniksi. Maahanmuuttajaoppilaat viihtyivät erityiskouluissa hyvin, he kokivat oman oppimisensa ja keskittymiskykynsä parantuneen erityiskoulun pienissä opetusryhmissä. Maahanmuuttajaoppilaat hyötyivät siitä yksilöllisestä tuesta, jota he olivat saaneet erityiskouluissa. Alaluokkalaisten maahanmuuttajaoppilaiden suhtautuminen erityiskouluun oli myönteisempää kuin yläluokkien maahanmuuttajaoppilaiden. Kaikissa erityiskouluissa maahanmuuttajaoppilaat kokivat asemansa luokassa hyväksi, tytöt vielä hiukan voimakkaammin kuin pojat. Opettaja-oppilassuhde koettiin hyväksi. Negatiivisena puolena maahanmuuttajaoppilaat kokivat koulukiusaamisen suuren esiintyvyyden erityiskouluissa. He olivat usein itse joko kiusaamisen kohteena tai kiusaajina. Maahanmuuttajaoppilaat uskoivat koulumenestymiseensä ja mahdollisuuksiinsa erityiskouluissa. He olivat yleisesti sitä mieltä, ettei erityiskoulu leimaa, joskin yläluokkien maahanmuuttajaoppilaat olivat empiväisempiä sen suhteen kuin alaluokkien maahanmuuttajaoppilaat. Tässä tutkimuksessa haluttiin tuoda maahanmuuttajaoppilaiden omat näkemykset esiin. Maahanmuuttajaoppilaita erityiskouluissa ei ole Suomessa juurikaan tutkittu, joten tutkimusaihe oli siltäkin osin uusi ja haastava.
Keywords: kouluviihtyvyys; kouluvaikeudet; oppilaat; erityskoulut; kotouttaminen; maahanmuuttajat; erityisopetus; koululaiset; monikulttuurisuus; koulunkäynti